Effects of behavioural competencies on emotional intelligence and teaching performance of university academics in Malaysia - Muda, Habsah (2015)
The purpose of this study was to examine the causal effect and the correlational relationship between the constructs of emotional intelligence (EI), behavioural competencies before, during, and after teaching delivery (BC-BDA-TD), as well as teaching performance (TP) in the context of public universities in Malaysia. In addition, the mediation effects of behavioural competencies before, during, and after the teaching delivery (BC-BDA-TD) construct were also investigated. On top of that, this study answered four research questions and tested four main hypotheses. The units of analysis were academic staff and students (1:3) from the faculty of business / management/ accounting / economics that derived from the three clusters of public higher learning institutions (research, focus, and comprehensive universities) in Malaysia. Hence, two sets of self-administered questionnaire surveys were established based on adoption and adaptation of theories / previous studies as the instrument for data collection. Besides, multi stages of sampling procedures (stratified, cluster, and simple random) were employed as the study involved a sample size of 226 academic staff and 592 students as respondents in this study. Furthermore, a statistical analysis using SPSS was employed to carry out a descriptive analysis on the demographic data. Other than that, as for inferential analysis, the Structural Equation Modelling (SEM) using AMOS was employed to answer the research questions and to test the hypotheses in this study. As a result, this study revealed that emotional intelligence (EI) had a significant and direct effect on teaching performance in the context of public universities in Malaysia. Hence, the two sub-dimensions of emotional intelligence, namely personal and social competence, significantly and directly affected their teaching performance. Moreover, the study had discovered that the two levels of teaching performance measured at the reaction (level 1) and learning (level 2) levels were significantly and directly influenced by an emotional intelligence of the academic staff. The findings also implied that the behavioural competencies of the academic staff before, during, and after the teaching delivery were directly influenced by the emotional intelligence of the academic staff, and further directly affected their teaching performance. Meanwhile, with the academic staffs’ behavioural competencies during teaching delivery as a mediator, the academic staffs’ emotional intelligence indirectly and completely affected their teaching performance. In fact, there was a ‘large effect’ of behavioural competencies by the academic staff during teaching delivery on their teaching performance. Therefore, the two sub-dimensions of ‘applying adult learning’ (AAL) and ‘demonstrating effective communication’ skill (DECS) were identified as significant under behavioural competencies during teaching delivery (BC-D-TD) in the context of this study. There was also a large mediation effect of academic staffs’ behavioural competencies during teaching delivery as a mediator between emotional intelligence and teaching performance. This exhibited that emotional intelligence among academic staff indirectly and partially affected their teaching performance through their behavioural competencies after teaching delivery (BC-A-TD). Apart from that, there was a small effect of academic staffs’ behavioural competencies after teaching delivery (evaluating students / ES) on their teaching performance. In contrary, there was a ‘large mediating effect’ of academic staffs’ behavioural competencies after the teaching delivery as a mediator between emotional intelligence and teaching performance. Thus, ‘evaluating students’ (ES) under the BC-A-TD had disclosed a ‘large effect’ in linking academic staffs’ emotional intelligence and teaching performance. Overall, these research findings supported all the hypotheses, answered the four research questions, and achieved the objectives set out in this study. With that, this study has successfully addressed the gaps found in previous studies, has contributed to the body of knowledge, as well as in providing useful implications to the public universities in Malaysia.